THE EFFECTIVENESS OF USING WORDWALL.NET AS WEB-BASED LEARNING TO ENRICH THE VOCABULARY OF THE EIGHTH-GRADE STUDENTS AT SMP NEGERI 1 TOMBARIRI - Igir, Gloria P.; Liando, Nihta V. F.; Andries, Fivy A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The objective of this research was to examine the effectiveness of utilizing wordwall.net as a web-based learning tool to enrich the vocabulary of the eighth-grade students at SMP Negeri 1 Tombariri. The primary inquiry of this research was: Can the use of wordwall.net be considered effective in enriching the vocabulary of the eighth-grade students at SMP Negeri 1 Tombariri? This research employed quantitative research, with quasi-experimental design. The subject of this research focused on eighth-grade students at SMP Negeri 1 Tombariri in class 8C, designated as the controlled class, and 8D, designated as the experimental class. The data were collected by a pre-test and post-test, which employed distinct questions but utilized the same test grid. The data analysis indicates a significant difference in the overall scores of the pre-test between the experimental class (1.255) and the controlled class (1.020). Meanwhile, the post-test total score indicated that the controlled class achieved a score of 1.395, while the experimental class achieved a score of 1.885. This research assessed the effectiveness of wordwall.net when implemented in the experimental classroom using the independent sample t-test feature of IBM SPSS software version 26. The utilization of wordwall.net demonstrated a significant impact, as indicated by a 2-tailed p-value of 0.001, which is less than the threshold of 0.050. The alternative hypothesis (Ha) has been affirmed, whereas the null hypothesis (H0) has been refuted. Thus, it can be inferred that the use of wordwall.net was considered effective in enriching students' vocabulary.